Propanol and 1, 3-propanediol enhance fatty acid accumulation synergistically in Schizochytrium ATCC 20888 - Wang, Tiantian; Wang, Fangzhong; Zeng, Lei; Guo, Pengfei; Wu, Yawei; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2023)
The effects of propanol and 1, 3-propanediol on fatty acid and biomass accumulation in Schizochytrium ATCC 20888 was explored. Propanol increased the synthesis of saturated fatty acids and total fatty acids, while 1, 3-propanediol elevated the synthesis of polyunsaturated fatty acids, total fatty acids and biomass. Although both of them quench ROS to increase fatty acids biosynthesis, the mechanisms are different. The effect of propanol did not reflect on metabolic level while 1, 3-propanediol elevated osmoregulators contents and activated triacylglycerol biosynthetic pathway. The triacylglycerol content and the ratio of polyunsaturated fatty acids to saturated fatty acids were significantly increased, which explained the higher PUFA accumulation in Schizochytrium after adding 1, 3- propanediol. At last, the combination of propanol and 1, 3-propanediol further elevated total fatty acids by approximately 1.2-fold without compromising cell growth. These findings are valuable for scale-up production of designed Schizochytrium oil for various application purposes.